Late Hellenistic and Roman tableware in the Aegean and the Black Sea region – Why we need chemical analysis - Schneider, Gerwulf; Daszkiewicz , Malgorzata (Rei Cretariae Romanae Fautorum Acta, 2022)
We need chemical analysis to unambiguously assign ceramic finds to archaeological wares. This is demonstrated using two examples: Eastern Sigillata C from Pergamon or Çandarlı (Pitane) and Pontic sigillata from the Crimea, analysed using WD-XRF. The analyses have to provide representative information about the raw materials used in the clay body from which the pottery was made. At least fifteen elements have to be determined with great precision and accuracy. This needs samples of about 1.5 grams to be taken, and generally rules out non-destructive chemical analysis. Homogeneous chemical reference groups enable the reliable definition of archaeological ceramic wares. Pottery provenance can be determined in those cases where analysed local material is available for comparison. The examples of ceramic finds suspected to be Pergamene sigillata found in Delos and Histria demonstrate the significance of chemical analysis. Reference groups for tablewares found in NW- and SE-Crimea include four groups of Pontic sigillata and Bosporan sigillata which are shown to be different to reference groups of Moesian sigillata.